Identification and characterisation of Aedes aegypti aldehyde dehydrogenases involved in pyrethroid metabolism - Lumjuan N. (Public Library of Science, 2014)
Background: Pyrethroid insecticides, especially permethrin and deltamethrin, have been used extensively worldwide for mosquito control. However, insecticide resistance can spread through a population very rapidly under strong selection pressure from insecticide use. The upregulation of aldehyde dehydrogenase (ALDH) has been reported upon pyrethroid treatment. In Aedes aegypti, the increase in ALDH activity against the hydrolytic product of pyrethroid has been observed in DDT/permethrin-resistant strains. The objective of this study was to identify the role of individual ALDHs involved in pyrethroid metabolism. Methodology/Principal Findings: Three ALDHs were identified; two of these, ALDH9948 and ALDH14080, were upregulated in terms of both mRNA and protein levels in a DDT/pyrethroid-resistant strain of Ae. aegypti. Recombinant ALDH9948 and ALDH14080 exhibited oxidase activities to catalyse the oxidation of a permethrin intermediate, phenoxybenzyl aldehyde (PBald), to phenoxybenzoic acid (PBacid). Conclusions/Significance: ALDHs have been identified in association with permethrin resistance in Ae. aegypti. Characterisation of recombinant ALDHs confirmed the role of this protein in pyrethroid metabolism. Understanding the biochemical and molecular mechanisms of pyrethroid resistance provides information for improving vector control strategies. © 2014 Lumjuan et al.